Management of the carotid artery stenosis in asymptomatic patients
Background: Moderate/severe carotid artery stenosis (CS) has a prevalence of 0.3 to 4.5% in women and 0.5% to 5.7% in men. The bifurcation of the common carotid artery turns this area vulnerable to atherosclerosis due to the features of haemodynamic flow. The exact prevalence of asymptomatic patients with CS remains to be unknown and there is a controversial opinion for the treatment of this patients. Objective: The authors aimed to review the evidence on the management of the asymptomatic CS and describe its clinical characteristics, diagnosis and treatment management. Results: The majority of patients with asymptomatic CS should be submitted to conservative management with best medical therapy. However, selective surgical management should be considered if high risk features are present. Conclusion: Medical intervention has an established role in the current routine management of persons with CS. Only extensive information allows tailored evidence-based decision.